Efficient and Chemoselective Procedure for Conversion of Rhodanine Derivatives into 1, 3‐Thiazolidine‐2, 4‐diones via 1, 3‐Dipolar Cycloaddition Reaction and Rearrangement Sequences. Issue 40 (27th October 2020) - Roosta, Atefeh; Alizadeh, Abdolali; Rezaiyehraad, Reze; Khanpour, Mojtaba
Abstract: Herein, we report a chemoselective 1, 3‐dipolar cycloaddition reaction between 5‐alkylidene‐ or 5‐arylidene rhodanine derivatives and nitrile oxide generated in situ from dibromoformaldoxime to construct 1, 3‐thiazolidine‐2, 4‐dione scaffold under mild conditions. This strategy exhibits a distinguished manner to afford thiazolidine derivatives in a simple, rapid and practical route. The results proved that the reaction proceeds through an unpredictable rearrangement and no spirocyclic product is generated. The structures of the target molecules were confirmed by IR, 1 H NMR, 13 C NMR, mass spectra and unambiguously X‐ray crystal structure analysis. Abstract : A new protocol for the synthesis of 1, 3‐thiazolidine‐2, 4‐diones based on the use of 1, 3‐dipolar cycloaddition reaction between rhodanine derivatives and nitrile oxide is proposed. This efficient and chemoselective procedure afforded the desired products in excellent yields (85–90 %). In this reaction, an unprecedented mechanism for the rhodanine substrates occurred and the resulting products were actually produced by replacing the thiocarbonyl group in the rhodanines with the carbonyl group.